Nature and Needs of Individuals with Autism Spectrum Disorders and Other Severe Disabilities: A Resource for Preparation Programs and Caregivers - Huckvale, Manina Urgolo; Van Riper, Irene (Rowman & Littlefield Publishers, 2016)
The book will focus on Autism Spectrum Disorders and Other Severe Disabilities (ASD/SD). Its purpose is to discuss the enhancement of the pedagogical skills of special education teachers who work specifically with students on the autism spectrum and have concurrent, significant intellectual disabilities. Due to the increase in diagnosis of autism, the editors recognize the need for teachers to have expertise working successfully with students on the spectrum. In the interest of pedagogical flexibility that the editors have explored options beyond, and in addition to, standard ABA guidelines. This book provides instructional strategies/methodologies for students on the low and high ends of the spectrum, as defined by the DSM, Fifth Edition, and with other concurrent severe disabilities